Influence of Comorbidities on Healthcare Expenditures and Perceived Physical and Mental Health Status Among Adults with Multiple Sclerosis: A Propensity Score-Matched US National-Level Study - Bhattacharjee S; Yegezu Z; Kollecas K; Duhrkopf K; Hashemi L; Greene N (Dove Medical Press, 2021)
Sandipan Bhattacharjee,1 Zufan Yegezu,2 Kristin Kollecas,3 Kevin Duhrkopf,3 Lobat Hashemi,3 Nupur Greene3 1Health Outcomes Division, College of Pharmacy, The University of Texas at Austin, Austin, TX, USA; 2Department of Pharmacy Practice and Science, College of Pharmacy, The University of Arizona, Tucson, AZ, USA; 3Neurology, Immunology, & Inflammation, Sanofi Genzyme, Cambridge, MA, USACorrespondence: Sandipan BhattacharjeeHealth Outcomes Division, College of Pharmacy, The University of Texas at Austin, 2409 University Ave., STOP A1930, Austin, TX, 78712-1120, USATel +1-512-471-6924Fax +1-512-471-8762Email Sandipan.bhattacharjee@austin.utexas.eduObjective: To evaluate the effect of comorbidities on healthcare expenditures and perceived physical and mental health status among adults with multiple sclerosis (MS) compared to propensity score-matched non-MS controls.Methods: A retrospective, cross-sectional, matched cohort study was conducted using Medical Expenditure Panel Survey (2005– 2015) data. The base study sample consisted of adults (age ≥ 18 years) who were alive and had positive total healthcare expenditures during the survey calendar year. Adults with MS were propensity-matched (1:1) to non-MS controls based on age, gender, and race/ethnicity using greedy matching algorithm. Healthcare expenditures consisted of total and subtypes of expenditures. Health status consisted of perceived physical and mental health status. Comorbidities were identified using ICD-9-CM and Clinical Classification System codes. Ordinary least squares regression and multinomial logistic regression were used to analyze the healthcare expenditures and health status variables, respectively.Results: Final study sample consisted of 541 adults in each MS and non-MS control groups after propensity score matching. After adjusting for potential confounders, individuals with MS had greater total and subtypes of expenditures compared to non-MS controls, and several comorbidities (eg, depression, hypertension) were significantly associated with increased healthcare expenditures. Yearly average total expenditures (expressed in 2018 US$) were significantly (p< 0.001) higher for adults with MS ($29,396) than propensity score-matched non-MS adults ($7875). Moreover, after adjusting for all individual-level factors, adults with MS experienced 363% (p< 0.001) higher total expenditures compared to propensity score-matched non-MS controls. Individuals with MS were more likely to report poorer physical and good mental health status compared to propensity score-matched non-MS controls, and several comorbidities (eg, anxiety, depression) were significant independent predictors of poorer health status. For example, adults with MS were four times more likely (OR: 4.10, 95% CI: 2.42– 6.96) to report fair/poor physical health status compared to excellent/very good physical health status compared with non-MS controls. Adults with MS were 42% (OR: 1.42, 95% CI: 1.01– 1.99) more likely than propensity score-matched non-MS controls to report good rather than very good or excellent mental health status. However, there was no difference between adults with MS and propensity score-matched non-MS controls in terms of reporting fair or poor than very good or excellent mental health status.Conclusion: Findings from this study indicate substantial economic and health status burdens among adults with MS at the US national-level that are significantly influenced by comorbidities.Keywords: multiple sclerosis, comorbidities, expenditures, physical health status, mental health status, propensity score matching